Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide

Breaking and making of rings: a method for the preparation of 4-quinolone-3-carboxylic acid amides and the expensive drug ivacaftor - Vasudevan, N.; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2015)
A simple and convenient method to access 4-quinolone-3-carboxylic acid amides from indole-3-acetic acid amides through one-pot oxidative cleavage of the indole ring followed by condensation (Witkop-Winterfeldt type oxidation) was explored. The scope of the method was confirmed with more than 20 examples and was successfully applied to the synthesis of the drug Ivacaftor, the most expensive drug on the market.
Keywords: Amides; Drug design; Fused-ring systems; Oxidation; Ozonolysis

First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine

Silicon incorporated morpholine antifungals: design, synthesis, and biological evaluation - Jachak, Gorakhnath R.; Ramesh, Remya; Sant, Duhita G.; Jorwekar, Shweta U.; Jadhav, Manjusha R.; Tupe, Santosh G.; Deshpande, Mukund V.; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Known morpholine class antifungals (fenpropimorph, fenpropidin, and amorolfine) were synthetically modified through silicon incorporation to have 15 sila-analogues. Twelve sila-analogues exhibited potent antifungal activity against different human fungal pathogens such as Candida albicans, Candida glabrata, Candida tropicalis, Cryptococcus neoformans, and Aspergillus niger. Si la-analogue 24 (fenpropimorph analogue) was the best in our hands, which showed superior fungicidal potential than fenpropidin, fenpropimorph, and amorolfine. The mode of action of sila-analogues was similar to morpholines, i.e., inhibition of sterol reductase and sterol isomerase enzymes of ergosterol synthesis pathway.
Keywords: Antifungal drugs; Candida albicans; ergosterol biosynthesis; morpholines; sila-analogues

Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Identification of new anti-inflammatory agents based on nitrosporeusine natural products of marine origin - Philkhana, Satish Chandra; Verma, Abhishek Kumar; Jachak, Gorakhnath R.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2017)
Nitrosporeusines A and B are two recently isolated marine natural products with novel skeleton and exceptional biological profile. Interesting antiviral activity of nitrosporeusines and promising potential in curing various diseases, evident from positive data from various animal models, led us to investigate their anti-inflammatory potential. Accordingly, we planned and synthesized nitrosporeusines A and B in racemic as well as enantiopure forms. The natural product synthesis was followed by preparation of several analogues, and all the synthesized compounds were evaluated for in vitro and in vivo anti-inflammatory potential. Among them, compounds 25, 29 and 40 significantly reduced levels of nitric oxide (NO), reactive oxygen species (ROS) and pro-inflammatory cytokines. In addition, these compounds suppressed several pro-inflammatory mediators including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF -kappa B), and thereby can be emerged as potent anti-inflammatory compounds. Furthermore, all possible isomers of lead compound 25 were synthesized, characterized and profiled in same set of assays and found that one of the enantiomer (-)-25a was superior among them. (C) 2017 Elsevier Masson SAS. All rights reserved.

Nitrosporeusine analogue ameliorates Chandipura virus induced inflammatory response in CNS via NF kappa b inactivation in microglia - Verma, Abhishek Kumar; Waghmare, Trushnal S.; Jachak, Gorakhnath R.; Philkhana, Satish Chandra; Reddy, D. Srinivasa; Basu, Anirban (PLOS Neglected Tropical Diseases, 2018)
Chandipura Virus (CHPV), a negative-stranded RNA virus belonging to the Rhabdoviridae family, has been previously reported to bring neuronal apoptosis by activating several factors leading to neurodegeneration. Following virus infection of the central nervous system, microglia, the ontogenetic and functional equivalents of macrophages in somatic tissues gets activated and starts secreting chemokines, thereby recruiting peripheral leukocytes into the brain parenchyma. In the present study, we have systemically examined the effect of CHPV on microglia and the activation of cellular signalling pathways leading to chemokine expression upon CHPV infection. Protein and mRNA expression profiles of chemokine genes revealed that CHPV infection strongly induces the expression of CXC chemokine ligand 10 (CXCL10) and CC chemokine ligand 5 (CCL5) in microglia. CHPV infection triggered the activation of signalling pathways mediated by mitogen-activated protein kinases, including p38, JNK 1 and 2, and nuclear factor kappa B (NF-kappaB). CHPV-induced expression of CXCL10 and CCL5 was achieved by the activation of p38 and NF-kappaB pathways. Considering the important role of inflammation in neurodegeneration, we have targeted NF-kappaB using a newly synthesised natural product nitrosporeusine analogue and showed incapability of microglial supernatant of inducing apoptosis in neurons after treatment.

Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

Access to a stereoisomer library of solomonamide macrocycles - Jachak, Gorakhnath R.; Athawale, Paresh R.; Choudhury, Rahul; Kashinath, K.; Reddy, D. Srinivasa (Chemistry-An Asian Journal, 2019)
In an attempt towards understanding stereo-structure activity relationships (SSARs), we have prepared eight possible stereoisomers of solomonamide macrocycles, in particular, by changing the stereochemical pattern of non-peptide fragment AHMOA. Here, we have demonstrated different ways to construct three contiguous chiral centers present in solomonamide B macrocycle using substrate/reagent-controlled methods. These methods involve Brown crotylation, NHK reaction and Evans aldol addition as key steps to synthesize key non-peptide fragment. Further, these non-peptide fragments were converted to their corresponding macrocycles via ligand-free intramolecular Heck reaction.
Keywords: Crotylation; Heck reaction; Inflammation; Macrocycles; Stereochemistry

Synthesis and biological evaluation of hoshionolactam-based compounds - Jachak, Gorakhnath R.; Elizebath, Drishya; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
In search of novel antitrypanosomal agents based on hoshinolactam (IC50=3.9 nM), we disclose the synthesis and biological evaluations of 14 different analogues of the natural product using combinations of different acids and lactams. Antitrypanosomal activity assays revealed that the synthesized analogues were less potent than the parent natural product.
Keywords: Hoshinolactam; Ozonolysis; Parasitic diseases; Trypanosoma

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.